what is the missing exponent that would make this equation true?

(k^(-5)*k^(2))/(kx)=(k^(0))^(-2)
a. x=-3
b. x=2
c. x=-5
d. x=0

1 answer

The missing exponent would be x=2. This is because when you simplify the equation by combining like terms, you get k^(-3)=k^(-2), which means that x=2. So the correct answer is b. x=2.
Similar Questions
  1. What is the missing exponent in the following equation?s⁵⁰⁰/s^? = s¹⁷⁵ Note: only type the exponent in the box, do
    1. answers icon 3 answers
  2. What is the missing exponent in the following equation?s⁵⁰⁰/s^? = s¹⁷⁵ Note: only type the exponent in the box, do
    1. answers icon 3 answers
    1. answers icon 1 answer
  3. What is the missing exponent that would make this equation true?k5⋅k2kx = (k2)−2 (1 point) Responses x = 6 x = 6 x = 9 x = 9
    1. answers icon 1 answer
more similar questions